2018
DOI: 10.7567/jjap.57.11ud05
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and ferroelectric polarization of tetragonal (Bi1/2Na1/2)TiO3–12BaTiO3

Abstract: We have investigated the crystal structure and ferroelectric polarization of (Bi 1/2 Na 1/2 )TiO 3 -12%BaTiO 3 by high-resolution neutron powder diffraction Rietveld analysis and density-functional theory calculations. It is revealed that the sample has a ferroelectric distortion in tetragonal P4mm symmetry along with a large tetragonality c/a of 1.022. The A-and B-site atoms exhibit a cooperative off-center displacement along the polar c-axis, which results in a large spontaneous polarization of 54 µC/cm 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The presence of preferential c-domains implies that the A-site ions of BNT-100xBT thick films easily move along polar-axes (tetragonal c-axis direction and hexagonal c-axis direction) by compressive stress. 10,12,40)…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The presence of preferential c-domains implies that the A-site ions of BNT-100xBT thick films easily move along polar-axes (tetragonal c-axis direction and hexagonal c-axis direction) by compressive stress. 10,12,40)…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Among them, (1-x)(Bi,Na)TiO 3 -xBaTiO 3 (BNT-100xBT) and related materials have been studied intensively because of their excellent electrical properties. [4][5][6][7][8][9][10][11]19,20) Superior electrical properties are observed for the BNT-100xBT ceramics in the MPB region (0.06 ⩽ x ⩽ 0.08), even though the T d in the MPB region is relatively low (110 °C-140 °C). Although the T d s in the composition x < 0.05 (rhombohedral R3c, ∼150 °C) and 0.09 < x (tetragonal P4mm, ∼160 °C) were higher than those in the MBP region, the T d s were still low for practical applications.…”
Section: Introductionmentioning
confidence: 98%
“…Although the T d s in the composition x < 0.05 (rhombohedral R3c, ∼150 °C) and 0.09 < x (tetragonal P4mm, ∼160 °C) were higher than those in the MBP region, the T d s were still low for practical applications. 19,[21][22][23] To overcome this problem in BNT-based ceramics, an increase in T d via lattice distortion caused by quenching has been reported. [4][5][6][24][25][26][27] Electronics devices are manufactured using various filmpreparation techniques, such as spin-coating and sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…29,[43][44][45][46][47][48][49][50][51] Among those, the tetragonal-like BiFeO 3 driven by epitaxial strain with large c/a ratio (~ 1.23) is of great interest due to its giant spontaneous polarization up to 150 µC/cm 2 . 42 Indeed, both theoretical calculations [52][53][54][55][56] and experimental studies 13,14,42,[57][58][59] Ion implantation, as a controllable defect engineering route, has enabled the ability to continuously tailor the structure phase transition, electric transport, magnetic properties, as well as band gap in epitaxial oxide thin films by driving the out-of-plane lattice expansion while leaving the in-plane lattice epitaxially locked to the substrate. [60][61][62][63][64] Very recently, it has also [65][66][67] However, the use of He implantation to simultaneously control phase transition and domain structure evolution in BiFeO 3 thin films remain elusive.…”
mentioning
confidence: 99%
“…29,[43][44][45][46][47][48][49][50][51] Among those, the tetragonal-like BiFeO 3 driven by epitaxial strain with large c/a ratio (~ 1.23) is of great interest due to its giant spontaneous polarization up to 150 µC/cm 2 . 42 Indeed, both theoretical calculations [52][53][54][55][56] and experimental studies 13,14,42,[57][58][59] have demonstrated that the ferroelectric oxides with giant tetragonality (or c/a ratio) possess a large polarization as a consequence of their large dipolar moment. However, despite considerable effort and dramatic progress in the research of tetragonal-like (Mc) BiFeO 3 , broad questions remain: (i) is it possible to stabilize the tetragonal-like phase BiFeO 3 in thick films while rhombohedral-like (R) phase generally emerges due to strain relaxation in the films thicker than ∼30 nm, 29 (ii) is there a pathway to achieve the theoretically predicted true tetragonal (T) phase with single domain state instead of the experimentally observed tetragonal-like Mc phase with multi-nanodomain structure in pure BiFeO 3 , (iii) could the c/a ratio (tetragonality) be further enhanced to obtain real supertetragonal (super T) phase BiFeO 3 that would lead to a larger spontaneous polarization?…”
mentioning
confidence: 99%